Efficacy of contrast enhanced computed tomography and diagnostic laparoscopy in detecting unsuspected peritoneal metastasis in gastric carcinoma - Singh, Hemanth Kumar; Elamurugan, T. P.; Sreenath, G. S.; N. R., Vishnu Prasad (International Surgery Journal, 2016)
Background:Gastric cancer remains the second most common cause of death from cancer worldwide. Peritoneal metastasis is the most frequent pattern of disease failure after curative resection of gastric cancer. Detection of these deposits and free cancer cells are necessary for predicting the risk of recurrence and prognostication. Methods: The study was conducted in Department of Surgery from October 2011 to July 2013. The study was designed as a prospective comparative study. All the patients diagnosed with gastric cancer by upper gastrointestinal endoscopy guided biopsy and not having clinical and / or radiological evidence of distant metastasis were included in the study. All patients underwent contrast enhanced computed tomography pre-operatively to detect metastatic disease or advanced gastric cancer. Subsequently the patients were planned for diagnostic laparoscopy followed by appropriate surgery. Sensitivities of the procedure in detecting peritoneal metastases was calculated and compared. Results:A total of 35 gastric cancer patients who met the inclusion and exclusion criteria were recruited in the study. The mean age of these patients was 53.5 years. Diagnostic laparoscopy detected 11 cases of metastatic diseases which were not picked up by CECT, which was statistically significant (p <0.05). Diagnostic laparoscopy showed adjacent organ infiltration in 18 patients, 9 of which were also identified on CT scan. Difference in detection of adjacent organ infiltration was not statistically significant. Infiltration of the serosal surface was seen in 31 patients and 9 of them were identified on CECT scan. Conclusions:Diagnostic laparoscopy is more sensitive and specific than current generation MDCT in detecting peritoneal metastasis and liver surface nodules in cases of gastric cancer. Diagnostic laparoscopy is also more specific in diagnosing the local infiltration into adjacent organs.